‘My Gaze as Sharp as a Pin / Penetrates the World’: The Colourful Dailiness in the Poetry of Zuzanna Ginczanka - Król, Karolina (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The aim of the paper is to present preliminary research results on the sight-centrism of the poetry written by Zuzanna Ginczanka. The author of the article draws attention to a paradox: it is the sight that is favoured in Ginczanka’s poems, and sight is traditionally perceived as ‘masculine’, intellectual, as opposed to ‘feminine’ senses that are more focused on touch. One of the more important features of sight-centrism in Ginczanka’s works is the observation of hues which may be found in the world. The paper investigates whether colours in this poetry change after the author of Of Centaurus moves to Warsaw. The consistency of poetic imagery placing the human being in natural landscapes rather than the urban space forces the researcher to reflect on the affiliation of Ginczanka with the Skamander group.